2019
DOI: 10.1038/s41598-019-41406-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome and in vitro analysis revealed anti-proliferative effect of citral in human stomach cancer through apoptosis

Abstract: Cancer is the second leading cause of death globally, particularly stomach cancer is third most common causes of cancer death worldwide. Citral possesses anti-tumor activity in various cancer cell lines, However its effect toward stomach cancer and its mechanism of action is have yet to be elucidated. The goal of the present study is to elucidate the role of citral in stomach cancer using transcriptome and in vitro approaches. We performed transcriptome analysis using RNA-seq and explored its capability to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Citral had an antiproliferative effect on several cancer cells. Apoptosis was observed in human stomach cancer cells [ 54 ]; in prostate cancer cells (PC3 cells) through upregulating BAX and downregulating Bcl-2 expression [ 55 ]; and in HCT116 and HT29 (colorectal cancer cell lines), in which it induced mitochondrial-mediated apoptosis via increased intracellular ROS and phosphorylation of p53 protein and the expression of Bax and decreased expression of Bcl-2 and Bcl-xL which promoted the cleavage of caspase-3 [ 56 ]; and citral also showed cytotoxicity in Burkitt's lymphoma cell line human and additively increased the cytotoxic and apoptotic effects of doxorubicin [ 57 ]. The combination of citral and doxorubicin increased the expression of the proapoptotic protein BAK but decreased the expression of the antiapoptotic protein BCL-XL compared to cells just treated with doxorubicin [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Citral had an antiproliferative effect on several cancer cells. Apoptosis was observed in human stomach cancer cells [ 54 ]; in prostate cancer cells (PC3 cells) through upregulating BAX and downregulating Bcl-2 expression [ 55 ]; and in HCT116 and HT29 (colorectal cancer cell lines), in which it induced mitochondrial-mediated apoptosis via increased intracellular ROS and phosphorylation of p53 protein and the expression of Bax and decreased expression of Bcl-2 and Bcl-xL which promoted the cleavage of caspase-3 [ 56 ]; and citral also showed cytotoxicity in Burkitt's lymphoma cell line human and additively increased the cytotoxic and apoptotic effects of doxorubicin [ 57 ]. The combination of citral and doxorubicin increased the expression of the proapoptotic protein BAK but decreased the expression of the antiapoptotic protein BCL-XL compared to cells just treated with doxorubicin [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding Cc_EO composition (Table 2), the primary phytochemical constituents are alpha-and beta-citral (37.23% and 28.91%, respectively). Citral is a natural compound possessing well-defined anti-tumor properties, especially in the case of breast carcinoma, stomach, and prostate cancers by inducing apoptosis and inhibiting metastasis [27][28][29][30]. Cc_EO exerted a strong in vitro anti-CRC effect at 75 Āµg/mL, in terms of cellular viability which decreased to 62.69% in Caco-2 cells and 46.58% in HT-29 cells following the 48 h treatment (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Fernando et al found that stigmast-5-en-3-ol from Dendronephthya gigantea exerted proapoptotic and anti-proliferative effects on MCF-7 human breast cancer cells [42]. Additionally, citral has been shown to inhibit the proliferation of breast cancer [43] and stomach cancer [44] cells. Moreover, by reducing the expression of glutathione, a Reactive Oxygen Species (ROS) scavenger, citral activates apoptosis of breast cancer cells [43], and in combination with curcumin, induces their apoptosis and cell cycle arrest [45].…”
Section: Discussionmentioning
confidence: 99%